An open-label randomized controlled trial of leflunomide in patients with acute SARS-CoV-2 omicron variant infection - Pan, Zhou; Wan, Zhihui; Wang, Yixuan; Zha, Shiqian; Zhang, Jingyi; Chen, Hao; Hu, Ke (Frontiers in Medicine, 2023)
Objective: To evaluate the efficacy and safety of leflunomide for the treatment of acute, symptomatic COVID-19.: A single-center, open-label, randomized controlled trial was performed during an outbreak of SARS-CoV-2 Omicron variant in December 2022. Symptomatic patients within five days of COVID-19 onset were randomly allocated to receive five days of either symptomatic treatment with leflunomide or symptomatic treatment alone. The primary endpoint was time to sustained clinical recovery. Results: Fifty-seven participants were randomized into two groups: 27 received leflunomide plus symptomatic treatment and 30 were assigned to symptomatic treatment alone. Participants treated with leflunomide had a shorter fever duration [3.0 (interquartile range [IQR], 2.0-4.0) days and 4.0 (IQR, 3.0-6.0) days, respectively (P=0.027)] and reduced viral shedding [7 (IQR, 6-9.5) days and 9.0 (IQR, 7.5-12.0) days, respectively, P=0.044)] compared with individuals treated with symptomatic treatment alone. However, there were no significant differences in time to sustained clinical recovery between the two groups [hazard ratio, 1.329 (95% confidence interval, 0.878-2.529); P = 0.207]. Conclusions: In acute adult COVID-19 patients presenting within five days of symptom onset, leflunomide combined with symptomatic treatment reduced fever duration and viral shedding time.